2010
DOI: 10.1016/j.compstruct.2009.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Machining FEM model of long fiber composites for aeronautical components

Abstract: This work is focused on the study of orthogonal cutting of long fiber composites. A model based in finite element was developed. The mechanisms of chip formation of Glass and Carbon Fiber Reinforced Polymer (FRP) composites were analyzed. Significant differences were observed when comparing machining induced damage predicted with the model for both materials. While damage extended widely ahead the interface and beneath the tool tip in the case of GFRP, damage was located in a much smaller zone in the case CFRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 21 publications
7
106
0
2
Order By: Relevance
“…The force increases for the across orientation. A similar behaviour was found for other composites CFRP and GFRP as it is shown in [49]. The orientation transversal to the plane also leads to increased values of the cutting force.…”
Section: Numerical Results: Validation and Discussionsupporting
confidence: 65%
“…The force increases for the across orientation. A similar behaviour was found for other composites CFRP and GFRP as it is shown in [49]. The orientation transversal to the plane also leads to increased values of the cutting force.…”
Section: Numerical Results: Validation and Discussionsupporting
confidence: 65%
“…The concept of degrading the stiffness of the composite in certain directions has been used in study composites failure including machining of composites [11,15,17]. In this study, the stiffness degradation values were adopted from [47] and are shown in Table 2.…”
Section: Stiffness Degradationmentioning
confidence: 99%
“…Material failure is governed by composite failure criteria. Different studies used various failure criteria, such as Tsai-Hill [8,10,14], maximum stress [10,11], Hashin [11,15,17]. Some studies [8][9][10] combined two failure mechanisms, primary failure for the onset of chip formation and a secondary failure for the progressive failure and completion of chip formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations